Extracoronal Splinting with Fiber-Reinforced Composites in Periodontitis Patient with Hypertension - Nadira Aqilla Adzra; Aprilia Yuanita Anwaristi; Sandi Mahputra (Universitas Muhammadiyah Semarang, 2026)
Background: One of the most common periodontal diseases is periodontitis. Periodontitis is a disease of periodontal tissue damage caused by the accumulation of microorganisms in the subgingival plaque that can cause periodontal pockets, loss of attachment, bleeding in the gingiva, and tooth mobility. Splinting can stabilize mobility teeth in periodontitis.Objective: this case report aims to discuss the treatment of extracoronal splinting, with fiber- reinforced composites in patients with chronic periodontitis accompanied by tooth mobility.Case: A 60-year-old man complained of dirty and rough teeth 1 year ago. Complaints are painless and never treated. The patient has a history of hypertension and daily smoking habits. After scaling and root planning treatment, grade 1 tooth mobility occurs in teeth 31, 41, and 42. One week later, an examination was carried out but showed no improvement, so splint treatment with fiber- reinforced composites was carried out on teeth 33 to 43. One week after the splinting treatment, an examination was carried out and the result was no tooth mobility in teeth 31, 41, and 42.Discussion: Splinting with fiber-reinforced composites has been shown to improve tooth stability is non- corrosive, easy to apply, requires low to medium cost, and has high aesthetics. Composite fiber materials have advantageous physical properties as they increase the flexural strength of composite resins.Conclusion: splint treatment with fiber-reinforced composites successfully stabilized tooth mobility in teeth 31, 41, and 42